(untitled) (Indian Journal of Case Reports, 2024)
Atypical hemolytic uremia syndrome (aHUS) is a rare, life-threatening disease, characterized by the same triad of hemolytic anemia, thrombocytopenia and renal failure as seen in hemolytic uremia syndrome (HUS). It differs in its etiology, being caused by a dysregulation of the complement pathway rather than Shiga-like toxin-producing Escherichia coli (STEC). Diagnosis is usually after exclusion of STEC infection and also thrombotic thrombocytopenic purpura (TTP). The prognosis of aHUS is poor, with 50% of cases progressing to end-stage renal disease and 25% resulting in mortality in the acute phase. The treatment of choice is plasma exchange which can lower mortality. Monoclonal antibody drugs such as eculizumab, which suppress the dysregulated complement pathway help to prevent complement mediated kidney injury, but such drugs remain prohibitively expensive.